A chair for my mother - Williams, Vera B. (New York : Greenwillow Books, 1982)
A child, her waitress mother, and her grandmother save dimes to buy a comfortable armchair after all their furniture is lost in a fire.
Caldecott Medal/Honor
Elem. School Library Collection
Wilson's Children
Book Links (A.L.A.), December 2002
Booklist, September 1995
Bulletin (Center for Children's books), May 2007
Keywords: Chairs -- Fiction; Family life -- Fiction; Saving and investment -- Fiction; Chairs -- Fiction; Family life -- Fiction; Saving and investment -- Fiction